Performing Body Positivity: A Dramaturgical Analysis of the Fat Acceptance Movement in Digital Spaces: Mengekspresikan Positivitas Tubuh: Analisis Dramaturgis Gerakan Penerimaan Tubuh Gemuk di Ruang Digital - Rasdica Denara Hernowo Puteri (CV. Media Publikasi Profesional, 2026)
This study aims to analyze the construction, production, and negotiation of the fat acceptance movement within digital spaces, utilizing visual communication practices and social media interactions. The research is important due to the increasing influence of digital platforms in shaping perceptions of the body, self-identity, and current beauty standards. Employing a qualitative approach with virtual ethnography, the study gathers data through digital observation of influencer content, analysis of audience comments, and visual documentation. Emerging patterns in communication and interaction were identified through a thematic analysis of the data. The results indicate that the fat acceptance movement operates as both a social campaign and a performative act. In this context, influencers strategically build identities using carefully selected visuals and positive narratives, while audiences engage by either supporting or challenging these interpretations. The research also highlights persistent conflicts between narratives of body acceptance and prevailing health discussions. The findings of this study advance digital sociology and the use of dramaturgical theory in online settings, while also informing the creation of more inclusive digital literacy practices. The originality of this study lies in its micro-interactional approach, integrating dramaturgical analysis to examine the dynamics of platform-based social movements